Maqasid Syariah Ibn ‘Asyur dan Pengukuran Kinerja Rantai Suplai Halal - Usman; Herry Subagyo; Sih Darmi Astuti, Sih Darmi Astuti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
Halal features in the halal supply chain provide the consequence that we need to use specific parameters to measure its performance. Therefore, maqasid al-sharia theory by Ibn ‘Asyur and the SCOR (Supply Chain Operations Reference) model are considered as the basis for developing a conceptual framework for measuring the performance of halal supply chain. Through the literature review, the dimensions of Ibn ‘Asyur's maqasid theory and the SCOR model were identified. With the content analysis approach, the results are obtained that all dimensions of the SCOR model can be mapped well to the dimensions of the Ibn ‘Asyur maqasid, but not vice versa. As one of the important and established dimensions in the maqasid al-sharia, religious protection is not mapped. Therefore the protection of religion represented by the sharia compliance principles must be determined as complementary to the SCOR model. The result is obtained a conceptual framework for measuring the performance of halal supply chains which consists of 7 main dimensions, namely: sharia compliance principles, reliability, response rates, agility, costs, efficiency, and human aspects.